Effective Dimensions of Medical Equipment Maintenance Management in Educational Hospitals: A Qualitative Study - Bahman Ahadinezhad; Omid Khosravizadeh; Aisa Maleki; Elnaz Ghanbari; Mahla Shafiei pour; Mahdi Safdari (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Medical equipment maintenance plays an important role in improving the equipment's function, increasing its effectiveness and efficiency, providing continuous health services, and improving the quality of services. This study is conducted to investigate the factors affecting medical equipment maintenance management. Methods: The present study was a qualitative investigation based on content analysis that was conducted in 2021. Data collection method was an open ended interview. The interviewees included all medical equipment operators and technicians of educational and medical centers affiliated with Qazvin University of Medical Sciences. The semi-structured interview guide was used as a data collection tool. Qualitative data obtained from interviews were analyzed by the content analysis method. The obtained coded were classified into dimensions and components using MAXQDA Software12 . Results: According to the findings, categories of time constraints, access to information, instructions and programs, type and number of equipment, financial constraints, user, patients, training programs, and equipment repair agencies were the most important factors affecting medical equipment maintenance management. Conclusion: Observing purchasing standards and guaranteed equipment, training all the staff involved, developing and explaining instructions and programs are essential for optimal equipment maintenance. These measurements will reduce the cost of repairing. g medical equipment and the need to purchase equipment; improve equipment, service quality performance, patient and user safety; and increase the device life.